Analisis Fungsi Denyut Nadi dalam Identifikasi Awal Henti Jantung pada Sistem Pertolongan Pertama - Muh Wahyuddin S Adam; Rahmawati Abjul; Faujiah Hatama; Meisti Hado; Siska Kaune (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Basic knowledge of first aid is an essential competency that must be possessed by prospective elementary school teachers, as teachers often act as first responders in medical emergencies at school. This study aims to analyze the function of the pulse in the early identification of cardiac core function as part of the first aid system. The method used is a qualitative descriptive approach through literature review from scientific sources related to cardiac anatomy and physiology, pulse examination techniques, and international first aid guidelines. The findings indicate that the pulse is a vital indicator reflecting the performance of the heart's core system, particularly the sinoatrial (SA) node and atrioventricular (AV) node. The absence of a detectable pulse signifies a serious disruption in the circulatory system and serves as the basis for emergency interventions such as cardiopulmonary resuscitation (CPR). In the context of elementary education, teachers need the skills to recognize and assess the pulse to make quick and accurate decisions during critical situations. Therefore, training in first aid skills, including pulse assessment, should be integrated into PGSD (Primary School Teacher Education) programs to prepare responsive and capable educators for emergency situations.